The antitumor activity of Bax BH3 peptide delivered by gold nanoparticles - Zhang, Xi; Yan, Qi; Wang, Jingying; Xu, Li; Guo, Yi (Frontiers in Materials, 2023)
Cancer has long remained one of the primary causes of disease and death globally, and it continues to pose a significant threat to human health. Surgery, radiotherapy, and chemotherapy are traditional treatments for cancer which are still widely used. However, while both surgery and radiotherapy remain acceptably effective in addressing a variety of primary tumors, neither possesses therapeutic potential for unknown metastatic lesions which may exist elsewhere in the patient’s body. Conversely, while systemic chemotherapy does have the potential for therapeutic efficacy on both primary and metastatic lesions alike, drug targeting is often poor, side effects are typically high, and treatment efficacy is still often lacking. Nanomedicine presents a promising solution to the above issues. For example, nanocarriers can be used to increase drug selectivity and targeting, increasing efficacy and decreasing side effects. Based on the role of the lethal domain of Bcl-2 family proteins, which play roles in apoptosis, the BH3-only protein, a section of BH3 peptide (abbreviated as BH3) with a sequence of Asp-Ala-Ser-Thr-Lys-Lys-Leu-Ser-Glu-Cys-Leu-Arg-Arg-Ile-Gly-Asp-Glu-Leu-Asp-Ser. However, treatments based on soluble BH3 peptides, as with those based on other biologically active macromolecules, exhibit low cell membrane permeability, poor stability against proteolysis, and low endosomal escape rates. In this paper, attempt to address these issues by developing a variety of BH3@gold nanoparticle drug systems with different coating ratios. We demonstrate, high loading efficiency and, excellent anti-tumor effects in vitro, including inhibition of proliferation and migration in the human lung adenocarcinoma cell line, A549. Our results present a new possibility for anticancer peptide drugs in the future.